HUBUNGAN MOTIVASI DIRI DENGAN KEPATUHAN PASIEN KANKER YANG MENJALANI KEMOTERAPI PADA SITUASI COVID-19 DI RSU SEMBIRING DELI TUA - Meta Rosaulina; Reisy Tane (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Cancer is a non-communicable disease that is a public health problem. Cancer is the first or second cause of death before the age of 70 in 91 countries out of 172 countries in the world. One of the treatments for cancer is chemotherapy. Giving chemotherapy treatment also has unpleasant side effects for the body and during the covid-19 pandemic, it greatly affects the motivation of patients to undergo chemotherapy treatment, there is high self-motivation, patients will want to undergo chemotherapy treatment and obey. The purpose of this study was to determine the relationship between self-motivation and adherence to cancer patients undergoing chemotherapy in the COVID-19 situation. The analytical descriptive research design was cross sectional. The number of samples in this study was 44 respondents using purposive sampling technique. The results of the chi square test statistic in this study showed that the p value p = 0.000 (<0.05) then Ha accepted that there was a significant relationship between self-motivation and adherence to cancer patients undergoing chemotherapy in the Covid-19 situation.